Tinjauan Yuridis Perlindungan Konsumen atas Pemadaman Listrik oleh Pln Batam - Alfis Setyawan; Vivi Marlina (Journal of Judicial Review, 2018)
The responsibility of electricity management in Batam, starting from generation, transmission, distribution to customer care lies on the hand of PT Pelayanan Listrik Nasional Batam (PLN Batam). However, these responsibilities do not include the constant supply of electricity and power outage which keeps occurring. Power outage occurrences resulted in inconveniences and monetary losses to consumer. The law regulates consumer protection but, has not been necessarily wellimplemented. Therefore, it is vital to investigate the legal protection of consumers on the unilateral power outage by PLN Batam that occurs in the field. The type of research used is empirical juridical. Primary data comes from interviews with PLN Batam, Yayasan Lembaga Konsumen Batam, as well as direct consumers; residents of Batam. Secondary data is derived from currently existing consumer protection law, alongside electricity law. From this research, it has been proven that power outage violated some consumer rights. Regarding this issue, more attention needs to be paid towards the implementation of consumers’ legal protection. Furthermore, preventive legal protection needs proper regulation and utilization. Also, there are obstacles that need to be addressed and overcome. This optimization can be achieved with awareness, coordination, and good faith by all parties involved in the relationship between PLN Batam and its customers.